1982
DOI: 10.1161/01.cir.65.1.141
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on heart rate in subjects free of heart disease. Studies by ambulatory electrocardiography and maximal exercise stress test.

Abstract: SUMMARY To delineate the effects of true aging, undetected heart disease and deconditioning on heart rate, we performed 24-hour ambulatory electrocardiography and maximal exercise stress test on 101 subjects with normal hearts. The maximal heart rate recorded was 180 beats/min; the minimum was 35 beats/min. A distinct diurnal pattern was observed.With increasing age, a decrease of the maximal heart rate achieved during exercise stress test (r = 0.27,p = 0.05) or spontaneously recorded during the day (r = 0.41,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
3
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(46 citation statements)
references
References 25 publications
9
30
3
2
Order By: Relevance
“…Previous cross-sectional HR studies in healthy adults showed that maximal HR on exercise, maximal and mean HR during Holter monitoring, and intrinsic HR after pharmacological autonomic block all decreased with age. [1][2][3][4] On the con- trary, our longitudinal study of 15 healthy elderly subjects at the mean age of 70 showed that the number of THBs was significantly increased 15 years later in most of the subjects (13 of 15 subjects). The increase in THB with age in healthy elderly subjects may derive from the decrease in cardiac output and total blood volume and respiratory dysfunction with aging, as well as from age-related changes in norepinephrine metabolism at the neuroeffector gaps in the sinus node and norepinephrine spillover from the synapses in heart and other organs to circulatory blood with age, 6,16,19,20) or from a decline in vagal activity due to a decrease in nitric oxide and muscarinic receptors with age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross-sectional HR studies in healthy adults showed that maximal HR on exercise, maximal and mean HR during Holter monitoring, and intrinsic HR after pharmacological autonomic block all decreased with age. [1][2][3][4] On the con- trary, our longitudinal study of 15 healthy elderly subjects at the mean age of 70 showed that the number of THBs was significantly increased 15 years later in most of the subjects (13 of 15 subjects). The increase in THB with age in healthy elderly subjects may derive from the decrease in cardiac output and total blood volume and respiratory dysfunction with aging, as well as from age-related changes in norepinephrine metabolism at the neuroeffector gaps in the sinus node and norepinephrine spillover from the synapses in heart and other organs to circulatory blood with age, 6,16,19,20) or from a decline in vagal activity due to a decrease in nitric oxide and muscarinic receptors with age.…”
Section: Discussionmentioning
confidence: 99%
“…Aging did not exert effects in such in vivo recordings in intact animals, which could be due to autonomic alterations known to increase sympathetic activation with age as has been observed in humans. 23,24 Interacting effects of aging and Scn5a disruption were observed in Poincaré plots representing HRV (Figure 2). Such HRV alterations are considered critically predictive of cardiac arrhythmic events in the form of ventricular tachycardia and sudden cardiac death.…”
Section: Hao Et Al Mouse Model Of Sinus Node Dysfunction 403mentioning
confidence: 98%
“…Also, the late-evening and early-morning onset could be linked to dilation of the left ventricle at lower heart rates in the supine position with elevation of filling pressure, which has been reported to be associated with nocturnal ischemia. 32 It is now established that persistently increased sympathetic activity causes desensitization and receptor down-regulation.33 This has been described in patients with heart failure34 and appears to occur with increasing age.35 Such down-regulation also may be present in smokers because normal subjects consuming 24 cigarettes during a 12-hour period have been reported to have a 45% rise in urinary excretion of norepinephrine and a higher heart rate during the day and night.36 Modulation of receptor sensitivity occurs quite rapidly37 and may be one explanation for the blunted morning peak and increased late peak of onset observed in this study among smokers compared with nonsmokers and for the absent morning peak among patients with a history of congestive heart failure and for those with previous myocardial infarction.…”
Section: Pathophysiologic Aspectsmentioning
confidence: 99%